Sviluppa la seguente potenza.
coefficienti del binomio;
(a + b)^n;
la somma degli esponenti di a e di b deve dare sempre 5;
per n = 5:
a = x; b = 3y;
(x - 3y)^5 =
= x^5 + 5 x^4 * (-3y)^1 + 10 x^3 *(-3y)^2 + 10 x^2 * (-3y)^3 +
+ 5 x^1 * (-3y)^4 +(-3y)^5;
= x^5 - 15 x^4 y + 90 x^3 y^2 - 270 x^2 y^3 + 405 x y^4 - 243 y^5.
Ciao @alby
COMB(5, 0) = 1
COMB(5, 1) = 5
COMB(5, 2) = 10
COMB(5, 3) = 10
COMB(5, 4) = 5
COMB(5, 5) = 1
(x - 3·y)^5=
=1·x^5 + 5·x^4·(- 3·y) + 10·x^3·(- 3·y)^2 + 10·x^2·(- 3·y)^3 +
+5·x·(-3y)^4 + 1·(- 3·y)^5=
=x^5 - 15·x^4·y + 90·x^3·y^2 - 270·x^2·y^3 + 405·x·y^4 - 243·y^5